"Walk in to Work Out": a randomised controlled trial of a self help intervention to promote active commuting. Issue 6 (1st June 2002) - Mutrie, N; Carney, C; Blamey, A; Crawford, F; Aitchison, T; Whitelaw, A
Abstract : Study objective: To determine if a self help intervention, delivered via written interactive materials (the "Walk in to Work Out" pack), could increase active commuting behaviour (walking and cycling). Design: Randomised controlled trial. The intervention group received the "Walk in to Work Out" pack, which contained written interactive materials based on the transtheoretical model of behaviour change, local information about distances and routes, and safety information. The control group received the pack six months later. Focus groups were also conducted after six months. Setting: Three workplaces in the city of Glasgow, Scotland, UK. Participants: 295 employees who had been identified as thinking about, or doing some irregular, walking or cycling to work. Main results: The intervention group was almost twice as likely to increase walking to work as the control group at six months (odds ratio of 1.93, 95% confidence intervals 1.06 to 3.52). The intervention was not successful at increasing cycling. There were no distance travelled to work, gender, or age influences on the results. Twenty five per cent (95% confidence intervals 17% to 32%) of the intervention group, who received the pack at baseline, were regularly actively commuting at the 12 month follow up. Conclusion: The "Walk in to Work Out" pack was successful in increasing walking but not cycling. The environment for cycling must be improved before cycling will become a popular option.